THE INFLUENCE OF COMPETENCY, CAREER DEVELOPMENT, COMPENSATION AND ORGANIZATIONAL COMMITMENT ON JOB SATISFACTION AND PERFORMANCE OF PUBLIC JUNIOR HIGH SCHOOL TEACHERS IN BANGKO DISTRICT, ROKAN HILIR REGENCY - Andi Andi; Julina Julina; Rizaldi Putra; Dominicus Josephus Swanto (International Conference on Business Management and Accounting, 2022)
This study aims to analyze the effect of competence, career development, compensation, and organizational commitment on job satisfaction and teacher performance at public junior high schools in The Bangko district. This research is quantitative research by distributing questionnaires to respondents. The population in this study were all public junior high school teachers in the Bangko district with ASN status. The sample selection technique uses the census method. The sample in this study amounted to 79 respondents. Data processing uses the Structural Equation Modeling (SEM) method with the SmartPLS application. The results of this study indicate that competence has a positive and significant effect on job satisfaction, career development has no significant effect on job satisfaction, compensation has a positive and significant effect on job satisfaction, organizational commitment has no significant effect on job satisfaction, competence has a positive and significant effect on teacher performance, career development has a negative and significant effect on teacher performance, compensation has no significant effect on teacher performance, organizational commitment has a positive and significant effect on teacher performance and job satisfaction has a positive and significant effect on teacher performance.